IMPLEMENTATION OF TEAMS GAMES TOURNAMENT WITH UTADIKA (SNAKES AND LADDER CHARACTER EDUCATION) IN BUILDING THE CHARACTER OF MUTUAL COOPERATION OF GRADE V STUDENTS OF SDN SUMUR WELUT III SURABAYA - Nadila Nur Fitria; Apri Irianto (Media Inovasi Pendidikan dan Publikasi, 2024)
The Arek Suroboyo School (SAS) program is an independent curriculum program that applies a new learning style so that students are more creative and comfortable in learning. This type of research is descriptive qualitative method research. The data collection technique used in this research is, using observation and interviews. The results of this research show that: Stages of Teams Games Tounament with (UTADIKA) Snakes and Ladders Character Education based on findings in the field shows that cooperation can be increased by using media as learning media can used as a means of learning while playing. Obstacles in forming the character of mutual cooperation in the Teams Games Tounament Stages with (UTADIKA) Snakes and Ladders Character Education for teachers, there is a lack of encouragement or awareness to work together and the use of dice made from foam which requires precise throwing, while for students with results Apart from the psychomotor aspect of learning, students will feel tired and fatigued easily, then when using dice made from foam, which requires precise throwing, and in carrying out the snakes and ladders mission, students will find it difficult..